INTEGRASI KONSEP KHALIFAH FIL ARDH DALAM KURIKULUM PENDIDIKAN AGAMA ISLAM: KAJIAN LITERATUR - Mulyani, Umi; Mila'il Ulya, Wazirotun; Amanatul Utami, Niki; Aliyah, Halul; Ana, Nurlaila (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Environmental damage, moral crisis, and low ecological awareness among students are important challenges in contemporary Islamic education. Islamic Religious Education (PAI) not only serves as a means of transferring religious knowledge but also has a strategic role in shaping the character of students who are environmentally responsible. The concept of khalifah fil ardh in Islam views humans as holders of Allah's mandate to maintain, manage, and preserve the earth sustainably. Therefore, integrating this concept into the PAI curriculum is crucial for building students' spiritual-ecological awareness. This study aims to analyze the concept of leaders on earth, its relevance in the PAI curriculum, and its integration model through an ecotheological approach in learning. This study uses a qualitative approach with library research and a literature review design. Data were obtained through documentation and literature studies from scientific journals, books, and relevant curriculum documents from 2020–2026. Data analysis was conducted using the interactive model of Miles and Huberman which includes data reduction, data presentation, and conclusion drawing. The results of the study indicate that the integration of the concept of khalifah fil ardh in the Islamic Religious Education curriculum can be achieved through strengthening ecologically-based learning materials, implementing ecotheology learning models, and establishing an environmentally conscious school culture. Learning models such as project-based learning, contextual learning, collaborative learning, and experience-based learning are considered effective in instilling the values of trust, responsibility, and environmental concern in students. Thus, the integration of the concept of khalifah fil ardh in the Islamic Religious Education curriculum contributes to shaping students who are religious, have ecological character, and have responsibility for environmental sustainability as an implementation of human duties as leaders on